Aortic valve leaflet assessment to inform novel bioinspired materials: Understanding the impact of collagen fibres on the tissue's mechanicam behaviour - Hughes, Celia Elizabeth; Lally, Caitriona (My University, 2025)
Aortic stenosis is a prevalent disease that is treated with either mechanical or bioprosthetic valve replacement devices. However, these implants can experience problems with either functionality in the case of mechanical valves or long-term durability in the case of bioprosthetic valves. To enhance next generation prosthetic valves, such as biomimetic polymeric valves, an improved understanding of the native aortic valve leaflet structure and mechanical response is required to provide much needed benchmarks for future device development. This study aims to provide such information through imaging and mechanical testing of porcine aortic valve leaflet tissue. Using second harmonic generation imaging on cleared tissue it is shown that the fibre orientations are dependent on the leaflet type (left coronary, right coronary, non-coronary), while fibre crimp is not solely dependent on either of these factors. Uniaxial tensile testing of the leaflets and their layers showed that the ventricularis layer is stiffer than the fibrosa but the fibrosa dominates the mechanical response of the whole leaflet due to its higher thickness. Overall, this work provides a detailed assessment of the native porcine aortic valve leaflets’ micro structure and mechanical response, delivering key information to aid the design and manufacture of future bioinspired valve implant devices.
PUBLISHED
Keywords: aortic valve; tavr; uniaxial tensile testing; second harmonic generation; microstructure; Next Generation Medical Devices; MICROSTRUCTURE; SECOND HARMONIC GENERATION; TAVR; Uniaxial tensile testing; aortic valve